An Update on Antioxidative Stress Therapy Research for Early Brain Injury After Subarachnoid Hemorrhage - Lin, Fa; Li, Runting; Tu, Wen-Jun; Chen, Yu; Wang, Ke; Chen, Xiaolin; Zhao, Jizong (Frontiers in Aging Neuroscience, 2021)
The main reasons for disability and death in aneurysmal subarachnoid hemorrhage (aSAH) may be early brain injury (EBI) and delayed cerebral ischemia (DCI). Despite studies reporting and progressing when DCI is well-treated clinically, the prognosis is not well-improved. According to the present situation, we regard EBI as the main target of future studies, and one of the key phenotype-oxidative stresses may be called for attention in EBI after laboratory subarachnoid hemorrhage (SAH). We summarized the research progress and updated the literature that has been published about the relationship between experimental and clinical SAH-induced EBI and oxidative stress (OS) in PubMed from January 2016 to June 2021. Many signaling pathways are related to the mechanism of OS in EBI after SAH. Several antioxidative stress drugs were studied and showed a protective response against EBI after SAH. The systematical study of antioxidative stress in EBI after laboratory and clinical SAH may supply us with new therapies about SAH.